Dual Active Bridge DC-DC Converter Based on Vector Control - Pinggang SONG; Jinghui TAN; Zhenbang ZHOU; Runjin ZHONG (机车电传动)
DAB (Dual Active Bridge) is the core devlce of replacing traditional transformers with power electronic transformers.In order to improve the dynamic response speed of DAB, a vector control strategy was proposed based on single-phase shift and two-level PWM model. By changing the high voltage side current of high frequency transformer into d-q coordinate vector, the output voltage and reactive current of low voltage side of DAB were controlled. The control method could improve the dynamic response speed, ensure the power balance and reduce the loss. Finally, the DAB vector control model was established on the Matlab/Simulink simulation platform. The results showed that DAB DC-DC converter has faster dynamic response speed and good control effect on reactive current under vector control strategy.